2018
DOI: 10.3389/fimmu.2018.02216
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteome and Cytokine Profiles Reveal Ceruloplasmin Eliciting Liver Allograft Tolerance via Antioxidant Cascades

Abstract: Acute rejection (AR) and spontaneous tolerance may occur after allograft orthotopic liver transplants (OLT) performed in certain combinations of donor and recipient rat strains, yet the underlying molecular cascades involved in these conditions remain poorly understood. Comprehensive analysis with proteomic tools revealed that ceruloplasmin was highly expressed during the tolerant period on day 63 post-OLT (POD 63) compared to the rejected samples on POD 14. Meanwhile, cytokine expression profiles implied that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…However, proteomic analysis has not been commonly used to study tolerance. The Chen group in Kaohsiung Chang Gung Memorial Hospital (Taiwan) has studied the proteomic signature of spontaneous tolerance in a rat model of LT (17,23,33). The rat models of tolerance can be induced spontaneously in LT between different strains (80).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, proteomic analysis has not been commonly used to study tolerance. The Chen group in Kaohsiung Chang Gung Memorial Hospital (Taiwan) has studied the proteomic signature of spontaneous tolerance in a rat model of LT (17,23,33). The rat models of tolerance can be induced spontaneously in LT between different strains (80).…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional gel electrophoresis (2D gel)-based proteomics is the most widely used strategy described in selected publications (50%); however, shotgun proteomics has displaced this strategy, as this proteomic method has been applied most frequently in the last 5 years (62.5%). Only four of the publications used antibody arrays, two of which were in combination with 2D gel-based proteomics analyses (20,33) (Table 2). The application of prefractionation techniques to reduce the high dynamic range in protein abundance is increasing, as we observed that their use has doubled in the last 5 years (62.5% vs.21.4%).…”
Section: Proteomics Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers suggest that CER plays a role in tolerance in organ transplantation as a regulator of inflammation and oxidative injury. 18 Both A2MG and CER are important in the maintenance of metal ion levels 19 while AT3 is the major inhibitor of proteases. All together these proteins are crucial to sustain the pulmonary defence against inhaled pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-DE gels were then transferred to a PVDF membrane which was incubated overnight at 4 °C with the primary antibody for DNPH (Molecular Probes, Eugene, Oregon, USA) or fibrinogen (DAKO, Santa Clara, CA, USA). The blots were washed and incubated with goat anti-rabbit IgG conjugated HRP for 2 h. Enhanced chemiluminescence (Millipore, Burlington, MA, USA) was applied for detection [40].…”
Section: Methodsmentioning
confidence: 99%